1991
DOI: 10.1104/pp.95.4.1063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diclofop and Diclofop-Methyl on Membrane Potentials in Roots of Intact Oat, Maize, and Pea Seedlings

Abstract: Growth and electrophysiological studies in roots of intact diclofop-methyl susceptible and resistant seedlings were conducted to test the hypothesis that the herbicide acts primarily as a proton ionophore. The ester formulafton of diclofop, at 0.2 micromolar, completely inhibited root growth in herbicide-susceptible oat (Avena Lucas et al. (16) and later revised by Wright and Shimabukuro (25), the ester form of diclofop crosses the plasmalemma and is rapidly hydrolyzed to the free acid form. This undissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…From these results, they concluded that the membrane response was a significant initial reaction in the eventual phytotoxic action of the herbicide. However, we recently provided evidence (DiTomaso et al, 1991) that casts some doubt on the relevance of the membrane response observed at relatively high concentrations of diclofop acid. We discovered that 100 FM diclofop acid was capable of depolarizing the E, of susceptible com and oat roots, as well as moderately tolerant barley roots and highly insensitive pea roots.…”
mentioning
confidence: 99%
“…From these results, they concluded that the membrane response was a significant initial reaction in the eventual phytotoxic action of the herbicide. However, we recently provided evidence (DiTomaso et al, 1991) that casts some doubt on the relevance of the membrane response observed at relatively high concentrations of diclofop acid. We discovered that 100 FM diclofop acid was capable of depolarizing the E, of susceptible com and oat roots, as well as moderately tolerant barley roots and highly insensitive pea roots.…”
mentioning
confidence: 99%
“…The demonstration of the nonselective effect of the graminicides (particularly the aryloxyphenoxypropionic acids) on the E,,, of susceptible and tolerant species (Figs. 1-3, and 5; DiTomaso et al, 1991) suggests that the membrane effect reported for these herbicides does not play an important role in their herbicidal activity under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this hypothesis, a membrane response should not occur in highly resistant dicotyledonous species at comparable concentrations. However, DiTomaso et al (1991) reported that 100 PM diclofop caused the same degree of depolarization of E, in diclofop-susceptible corn and diclofop-resistant pea. Furthermore, they showed that a 96-h exposure to 0.8 HM diclofop completely inhibited corn root growth but did not depolarize root cortical cell E, .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryloxy phenoxy propionic acid herbicides are one of the major pesticide groups. Diclofop-methyl is a selective, post emergence aryloxy phenoxy propionic acid herbicide primarily used to control wild oat (Avena fatua L.) and other annual graminaceous weeds in wheat, barley, and soybeans [3,17]. Exposure to some of these pesticides may lead to modifications in the genetic material thereby causing mutagenicity, carcinogenicity, teratogenicity and immunotoxicity [16].…”
Section: Resultsmentioning
confidence: 99%